Factors Connected with the Profitability of Small and Medium Enterprises in Eldoret Municipality, Kenya - Bogonko , Jared Bitange (African Journal of Education,Science and Technology (AJEST), 2015)
The study investigated the relationship between profitability, bank loans, age of business and the size of small and medium enterprises in Eldoret Municipality, Kenya. Using fixed-effects regression model, the paper was based on a balanced panel data of 115 SMEs of existing firms that have taken loans or currently have active loans, randomly selected in Eldoret Municipality, Kenya. The equation specified profitability as dependent variable and loans, sales, age of business, size of business and interest rate as independent variables. All the data except interest rate have been derived from the primary source/field survey. The results demonstrate that there is interdependence between the SMEs profitability and bank loans, and a significant relationship between profitability and the size of business. For high profitability, increased loans and growth in size of business remain important. The study recommends that the government should formulate policies that will compel commercial banks to relax their restrictive regulations and operations which discourage borrowing, and offer more credit facilities for SMEs. The government should empower the SMEs to access and get credits from the commercial banks through formal and informal entrepreneurship education. The researcher‘s desire is that this study will stimulate debate on Government policy in relation to profitability and growth of SMEs and through that galvanize public and government support for SME. The study will provide descriptive findings of government policy and SME profitability and will demonstrate the simultaneous impact of financial management practices. In addition, the research study will provide a model of government policy and SME growth and profitability, in which policy will be related to SME growth and profitability.